Prediction and prevention of thromboembolic events with enoxaparin in cancer patients with elevated tissue factor‐bearing microparticles: a randomized‐controlled phase II trial (the Microtec study). (13th December 2012) - Zwicker, Jeffrey I.; Liebman, Howard A.; Bauer, Kenneth A.; Caughey, Thomas; Campigotto, Federico; Rosovsky, Rachel; Mantha, Simon; Kessler, Craig M.; Eneman, Jonathan; Raghavan, Vidya; Lenz, Heinz‐Joseph; Bullock, Andrea; et al.
Summary Elevated levels of circulating tissue factor‐bearing microparticles (TFMP) have been associated with an increased risk of developing venous thromboembolism (VTE) in cancer patients. We performed a randomized phase II study to evaluate the cumulative incidence of VTE in advanced cancer patients with lower levels of TFMP not receiving thromboprophylaxis and those with higher levels of circulating TFMP randomized to enoxaparin or observation. The cumulative incidence of VTE at 2 months in the higher TFMP group randomized to enoxaparin (N = 23) was 5·6% while the higher TFMP group observation arm (N = 11) was 27·3% (Gray test P = 0·06). The cumulative incidence of VTE in the low TFMP was 7·2% (N = 32). No major haemorrhages were observed in the enoxaparin arm. The median survival for patients with higher levels of TFMP followed by observation was 11·8 months compared with 17·8 months on enoxaparin (P = 0·58). In a prospective randomized trial, increased numbers of circulating TFMP detected by impedance flow cytometry identified cancer patients with a high incidence of VTE. Enoxaparin demonstrated a clear trend towards reducing the rate of VTE in patients with elevated levels of TFMP, with an overall rate of VTE similar in magnitude to the lower TFMP group.